2021
DOI: 10.2147/vmrr.s331968
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Staphylococcus aureus, Methicillin-Resistant Staphylococcus aureus and Potential Risk Factors in Selected Dairy Farms at the Interface of Animal and Human in Bishoftu, Ethiopia

Abstract: Background Staphylococcus aureus ( S. aureus ) has been reported as the most commonly isolated highly contagious pathogen from human, animals and animal products. Methicillin-resistant Staphylococcus aureus (MRSA) has emerged as a significant pathogen with zoonotic potential that could have devastating consequence for the health and well-being of animals and human. Methods A cross-sectional study was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
4
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 33 publications
(60 reference statements)
6
4
3
Order By: Relevance
“…These ndings are in agreement with a study which reported 100% MDR and resistance to at least two antibiotics among human isolates in a hospital survey in Ethiopia (12). The prevalence pro les of AMR reported here are similar to those by Tibebu etal who reported 94% prevalence to penicillin and 92% to ampicillin for cattle isolates (14). Likewise, a study by Rao et al, (2022) reported AMR prevalence of 81.6% to Penicillin among human isolates.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These ndings are in agreement with a study which reported 100% MDR and resistance to at least two antibiotics among human isolates in a hospital survey in Ethiopia (12). The prevalence pro les of AMR reported here are similar to those by Tibebu etal who reported 94% prevalence to penicillin and 92% to ampicillin for cattle isolates (14). Likewise, a study by Rao et al, (2022) reported AMR prevalence of 81.6% to Penicillin among human isolates.…”
Section: Discussionsupporting
confidence: 92%
“…Likewise, a study by Rao et al, (2022) reported AMR prevalence of 81.6% to Penicillin among human isolates. The level of resistance of both cattle and human S. aureus isolates to Fluoroquinolones and Aminoglycosides was relatively low, a nding which was similar to that reported by Tibebu et al, (2021). The AMR prevalence ndings of this study could probably be explained by the trend of routine injudicious overuse of particular antibiotics compared to others.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Among mastitis-causing bacteria, S. aureus represents the main causative agent that threatens the farmers not only due to the high incidence rate and zoonotic potential but also due to reports of multi-drug resistance [7][8][9][10]. Whereas E. coli is among the gram-negative bacteria that often cause subclinical mastitis affecting the performance of dairy on top of its public health risks.…”
Section: Introductionmentioning
confidence: 99%
“…However, PCR-based detection of the mecA gene is still the gold standard for identifying MRSA isolates [27,28]. Several studies were carried out in Ethiopia to identify the presence of MRSA infections in various regions of the country [29][30][31][32][33][34][35][36]. However, information about MRSA from raw milk and farm workers is still rare.…”
Section: Introductionmentioning
confidence: 99%